Systematic Literature Review: The Role of Islamic Religious Education Teachers in Instilling Religious Moderation in Elementary Schools - Siskha Putri Sayekti (Bulletin of Islamic Research, 2023)
Religious moderation plays a crucial role in fostering tolerance and harmony in diverse societies. In Indonesia, the need to instill religious moderation in young learners has become increasingly vital, particularly in elementary schools, where foundational values are formed. This study examines the role of Islamic Religious Education (PAI) teachers in promoting religious moderation among elementary school students. Through a descriptive qualitative approach, this research reviews existing literature on the implementation of religious moderation within the PAI curriculum and the strategies employed by teachers to instill these values. The findings suggest that PAI teachers are pivotal in shaping students' attitudes toward religious tolerance, using strategies such as role modeling, promoting respect through group discussions, and creating religious habituation programs. The study concludes that effective Islamic religious education can foster an inclusive, tolerant, and harmonious school environment, contributing to the broader goals of national unity and interfaith respect. This paper highlights the importance of PAI teachers as facilitators of moderation, emphasizing their role in guiding students to appreciate religious diversity and live harmoniously in a multicultural society.